Mobile Projection-based Augmented Reality in Work Environments – an Exploratory Approach - Büttner, Sebastian; Besginow, Andreas; Prilla, Michael; Röcker, Carsten (Workshop on Virtual and Augmented Reality in Everyday Context (VARECo), Mensch und Computer 2018)
Projection-based Augmented Reality (AR) might change the interactions with digital systems in future work environments. A lot of stationary projection-based AR assistive systems have been presented that might support future work processes. However, not much research has been done beyond stationary settings. With moving towards mobile settings, fast and robust object recognition algorithms are required that allow real-time tracking of physical objects as targets for the projected digital overlay. With this work, we present a portable projection-based AR platform that recognizes objects in real time and overlays physical objects with in-situ projections of digital content. We consider our system as a precursor to a future mobile projection-based assistive system. By presenting the system, we want to start a discussion in the HCI community about the potential of mobile projection-based AR in future work environments.